A single trunk-mounted wearable sensor to measure motor performance in triathletes during competition - Chesher, S. M.; Rosalie, S. M.; Chapman, D. W.; Charlton, P. C.; van Rens, F. E. C. A.; Netto, K. J. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2024)
The objective of this research was to validate a single, trunk-mounted wearable sensor (Optimeye S5, Catapult Australia, Melbourne) to measure the cadence of swimming strokes, cycling pedals and running strides in a triathlon. While similar validations have been performed in swimming and running, it is a novel application in cycling, and thus, across a whole triathlon. Seven triathletes were recruited to participate in a sprint distance triathlon which was filmed and simultaneously measured by a single, trunk-mounted wearable sensor. To validate the wearable sensor, individual swimming strokes, cycling pedal strokes and running strides were manually counted by viewing the wearable sensor data and video footage. While analysing cycling data, changes in cycling subtask performances were noticed, thus, a secondary analysis in cycling was conducted to investigate. The 95% limits of agreement analysis indicated the sensor validly measured swimming strokes (mean bias = -0.034 strokes), cycling pedal strokes (mean bias = -0.09 strokes) and running strides (mean bias = 0.00 strides) with minimal to no bias (p > 0.05). Further analysis of cycling revealed the wearable sensor is an acceptably valid tool to measure the duration of out of saddle riding (mean bias = 0.08 s), however, significant differences in the duration of in saddle riding (mean bias = -0.5 s) and coasting were identified (mean bias = 0.39 s). A single trunk mounted wearable sensor is a valid tool to measure movement cadence in a triathlon, however, further validation is required to generate a full understanding of cycling subtask performances.